Telemedicine consultations with physicians in Swedish primary care: a mixed methods study of users' experiences and care patterns - Felicia Gabrielsson-Järhult; Sofia Kjellström; Kristina Areskoug Josefsson (Taylor & Francis Group, 2021)
Objective The study aimed to explore users' experiences and care patterns concerning telemedicine consultations with physicians in Swedish primary care from 2017 to 2019. Design and participants: A mixed methods study involving 26 qualitative interviews with users of telemedicine consultations from a national sample, complemented by a quantitative registry study of data from 10,400 users in a Swedish region. Results Users mainly described telemedicine consultations as a positive experience and perceived that the service met their current health care needs. Users also valued high accessibility, timesaving, and the contribution to ecological sustainability. Users felt competent about choosing when to use telemedicine consultations, most commonly for less severe health care concerns. This was confirmed by the quantitative results; only a few users had other care contacts within physical primary care before, or after, the telemedicine consultation, attended acute care or phoned 1177 Health Care Guidance. Conclusions This study provides a rare account of users' experiences of telemedicine consultations. Users expressed satisfaction with this up-to-date use of health care resources for them as individuals, the health care system, and the environment. Telemedicine consultations were perceived as efficient and safe according to users. In addition, the study shows a low degree of further physical contacts in primary care or in acute care related to the telemedicine consultations.Key points Users have positive experiences of telemedicine consultations with physicians and experienced that the service had meet their actual needs for health care. Users were mainly satisfied with the service and highlighted the value of high accessibility. Users experienced that telemedicine consultants provided an alternative care service for mostly minor health problems, perceiving them to save time and resources for themselves, the health care system, and the environment. Most telemedicine consultations did not result in additional contacts with 1177 Health Care Guidance, physical visits to primary care, or acute health care. Telemedicine consultations with physicians were mainly used by persons aged 0-30 years and need to be further developed to suit other age groups.